Opioid Prescription Consumption Patterns After Total Joint Arthroplasty in Chronic Opioid Users Versus Opioid Naive Patients. (June 2020) - Kaidi, Austin C.; Lakra, Akshay; Jennings, Emma L.; Neuwirth, Alexander L.; Geller, Jeffrey A.; Shah, Roshan P.; Cooper, H. J.; Hickernell, Thomas R.
Abstract : Background: Although chronic preoperative opioid use has been linked to inferior total joint arthroplasty outcomes, little research exists on postoperative prescribing patterns for opioid-naive orthopaedic patients versus chronic opioid users. Method: The New York State Prescription Monitoring Program database, which tracks controlled prescriptions dispensed in-state over the preceding 12 months, was retrospectively queried for 386 patients who underwent primary, elective total hip or knee arthroplasty at a high-volume, urban medical center from May through December 2017. Seventy-four patients were excluded because they did not return prescription monitoring program results, leaving 312 patients. Prescribers, medications, dates prescribed and filled, and quantity dispensed were recorded 3 months preoperatively through 12 months postoperatively. We defined chronic users as ≥2 opioid prescriptions filled in 3 preoperative months and opioid-naive as <2 filled. Opioid use was compared univariately using 2-tailed Student t -tests. Results: Chronic opioid users (n = 49; 15.7%) filled an average of 13, 006.64 morphine equivalent doses per patient in the 12-month postoperative period, while opioid-naive users (n = 263; 84.3%) filled an average of 854.48 morphine equivalent doses per patient ( P < 0.01). Opioid use in the chronic-user group was significantly higher in each 6-week postoperative interval ( P < 0.01). These trends remained significant when stratified by procedure. For opioid-naive patients, 74% of opioid prescriptions were prescribed by our orthopaedic department. For chronic users, only 21% of opioid prescriptions originated from our department. Chronic users were found to cyclically fill opioid prescriptions every 3 to 4 weeks postoperatively as far out as 12 months and were significantly more likely to fill nonopioid controlled substance prescriptions both preoperatively and postoperatively ( P < 0.01). Discussion: Chronic opioid users undergoing arthroplasty filled significantly more opioid prescriptions than opioid-naive patients. Chronic users obtained prescriptions from myriad sources, only a minority of which originated from our orthopaedic department. In the current opioid epidemic, vigilance regarding opioid prescribing is critical.